Alteration of Diffusion Capacity After SARS-CoV-2 Infection: A Pathophysiological Approach - Frija-Masson, Justine; Bancal, Catherine; Plantier, Laurent; Benzaquen, Hélène; Mangin, Laurence; Penaud, Dominique; Arnoult, Florence; Flamant, Martin; d’Ortho, Marie-Pia (Frontiers in Physiology, 2021)
SARS-CoV-2 infection has affected millions of people worldwide and pneumonia affects 90% of patients. This raises the possibility of millions of people with altered lung function. Few data exists to date on pulmonary function after SARS-CoV-2 infection, but alteration of diffusion capacity of CO (DLCO) is the most frequently described abnormality. First, we review existing data on DLCO alteration after SARS-CoV-2 infection and discuss the implication of restrictive disorder in DLCO alteration. Second, we discuss the pathophysiology of DLCO alteration, and try to disentangle vascular damage and fibrosis. Last, we present original data on the effect of using European Coal and Steel Community (ECSC) or Global Lung Function Initiative (GLI) reference equations to diagnose diffusion capacity alteration three months after SARS-CoV-2 infection.